Kebijakan Formulasi dan Prospektif Penegakan Hukum Tindakan Kealpaan Tenaga Medis/Tenaga Kesehatan (Dinamika Pertanggungjawaban Pidana dalam Malpraktik Medis) - Godeliva Ayudyana Suyudi; Dina Tsalist Wildana; Sapti Prihatmini; Galuh Puspaningrum (Jurnal Pembangunan Hukum Indonesia, 2025)
Article 440 of the Health Act formulates criminal penalties for the negligence of medical persons/health workers in health services that result in serious injury or death. This study aimed to examine the urgency of the special provision formulation policy and its prospective law enforcement. This framework creates the general provisions of the Criminal Code applied in dealing with negligent acts of medical personnel/health workers resulting in serious injury or death of patients, which should be overridden based on “lex specialis derogat legi generali” principles. Health act in Article 440 as a material offence has special characteristics, whose assessment is based on professional standards and is oriented towards providing balanced legal protection for patients, health workers, and legal certainty for law enforcement officials. According to proving the elements of negligence and causal relationship in the context of therapeutic transactions, it is based on evidence according to KUHAP. Expert testimony occupies an important position in determining professional standards, including medical records and/or visum et repertum. As a material offense, Health Law Article 440 requires caution to achieve the goals of material truth and justice. It can be concluded that the law enforcement of negligence of medical/health workers must be based on the specificity of the unlawful nature of the act, which is different from general criminal offenses, with the benchmark of professional standards resting on the causal relationship between negligence and consequences through evidence, especially expert testimony.